Effects of crosslinking degree and carbon nanotubes as filler on composites based on glycidyl azide polymer and propargyl‐terminated polyether for potential solid propellant application. Issue 39 (22nd June 2017) - Wang, Song; Liu, Changhua; Guo, Xiang; Tang, Gen; Gan, Lin; Qi, Chun; Huang, Jin
ABSTRACT: Triazole crosslinked polymers were prepared by reacting glycidyl azide polymer (GAP) with the propargyl‐ terminated poly(tetramethylene oxide) (PTMP) at different molar ratios of azide versus alkyne. Based on the optimum mechanical properties of the GAP/PTMP‐ 2.5, a series of GAP/PTMP nanocomposites reinforced by either multi‐ walled carbon nanotubes (MWCNTs) or carboxy‐ functionalized multiwalled carbon nanotubes (MWCNTs‐ COOH) were prepared with different mass ratios. The glass transition temperatures ( Tg, PTMP ) assigned to PTMP of the GAP/PTMP composites almost kept at a constant range when the molar ratio of azide versus alkyne was from 1.0 to 2.5. When the loading MWCNTs was 1.0 wt %, the tensile strength and elongation at break achieved a maximum of 1.77 MPa and 36.3%, respectively. The nanocomposites with nearly similar Tg, PTMP indicated no phase separation in the crosslinked polymers. The results revealed that the improved properties of GAP‐ based materials could be achieved by changing the molar ratio of azide versus alkyne and the nanofillers content. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45359. Abstract :